Design for culvert blockage: the ARR 2016 guidelines. Issue 1 (2nd January 2018) - French, Robert; Jones, Malcolm
ABSTRACT: Book 6 Chapter 6 of the 2016 edition of 'Australian Rainfall and Runoff' contains design guidelines for the hydraulic design of culvert and bridge waterways to mitigate the effects of obstruction by flood-borne debris. Any such obstruction causes undetectable rises to peaks in the vast majority of over-bank floods, which are the only ones of concern to the general public. Discussion on the design guidelines shows that they are unnecessary. The data-free basis of the blockage design guidelines and their unproven ability to predict blockages make questionable any economic justification of the guidelines' requirement for increased waterway sizes in watercourse crossing structures.